Pemikiran Ekonomi Kontemporer Madzhab Alternatif Tawaran dari Timur Kuran - Aris Saiful Mizan; Arif Angga Bayu Saputro; Mugiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The understanding of the alternative economic school proposed by Timur Kuran is a study that encompasses various approaches and models different from the conventional economic system. The focus of the alternative economic school is to create a more just, sustainable, and human and environmentally oriented system. This research aims to explore the contemporary economic thoughts of the alternative school of Timur Kuran. The method used in this research is literature review with descriptive analysis. Timur Kuran asserts the superiority of Islamic economic theory and highlights economic practices aligned with Islamic principles as a response to the imbalances and injustices within the capitalist system. The goal is to enhance the economy and strengthen Islamic identity amid cultural globalization. Moreover, he rejects the concept of interest based on the fundamental principle of Islamic economics, the prohibition of usury, deeming it exploitative and unjust in wealth distribution. Kuran also criticizes the zakat redistribution system, questioning its effectiveness and pointing out inadequacies in fund management and allocation, leading to limited impact in addressing poverty.